2013
DOI: 10.1108/srj-05-2011-0110
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing corporate social responsibility: effects on corporate reputation, culture, and legitimacy in Malaysia

Abstract: Purpose: The purpose of this paper is to develop measures of Asian corporate social responsibility (CSR) based on David's dual process model for Malaysian government linked corporations (GLC) and publicly listed companies (PLC). Design/methodology/approach: A survey consisting was conducted and a structural equation model was used to test the relationships among constructs. An instrument to measure CSR practices focusing on CSR relational, CSR ethical/moral, and CSR discretionary is developed to evaluate impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 56 publications
3
49
0
1
Order By: Relevance
“…Thus, perceptions of a firm's stance on CSR are influenced by its corporate marketing efforts including branding, reputation building, and communications [141]. This finding strongly supports the evidence provided by Abdullah and Aziz [142] whereby CSR antecedents emerged through formalization of corporate communication management in Malaysian organizations, which directly impacted corporate reputation. Thus, Malaysian construction firms should emphasize on CSR marketing.…”
Section: Effective Csr Communicationsupporting
confidence: 76%
“…Thus, perceptions of a firm's stance on CSR are influenced by its corporate marketing efforts including branding, reputation building, and communications [141]. This finding strongly supports the evidence provided by Abdullah and Aziz [142] whereby CSR antecedents emerged through formalization of corporate communication management in Malaysian organizations, which directly impacted corporate reputation. Thus, Malaysian construction firms should emphasize on CSR marketing.…”
Section: Effective Csr Communicationsupporting
confidence: 76%
“…A total of eight articles investigated the impact of social responsibility on different organizational level variables (e.g. Boehe & Cruz, ; Abdullah & Abdul Aziz, ; Reverte et al, ), Singhapakdi et al, ), seven articles evaluated the influence of social responsibility on customer‐related variables (e.g. de los Salmones et al, ; Ellen et al, ; Sen & Bhattacharya, ), and six articles examined the influence of social responsibility on employee‐related variables (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show a positive relationship between MNEs' CSR and their corporate reputation. Although some studies did not find evidence for a clear influence of CSR on reputation (Park et al, ; Valenzuela‐Fernández et al, ), most prior research has shown that CSR initiatives influence reputation positively (Abdullah and Abdul Aziz, ; Fombrun and Shanley, ; Turban and Greening, ). For example, Fombrun and Shanley () found that stakeholders assign higher reputations to firms that give proportionally more to charity than other firms, and Turban and Greening () concluded that corporate social performance was related to firms' reputations and attractiveness as employers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%